Implikasi Yuridis dan Dampak Psikologis Perkawinan Beda Agama Terhadap Tumbuh Kembang Anak - Wike Sundari; Heri Firmansyah (Ahlana: Jurnal Hukum dan Hukum Keluarga Islam, 2026)
This study examines the legal implications and psychological impacts of interfaith marriage on children’s growth and development in Indonesia. Interfaith marriage is a phenomenon that emerges within a plural society as a result of increasing cross-religious social interactions. However, its regulation within Indonesian positive law remains debatable, particularly after the issuance of Supreme Court Circular Letter (SEMA) No. 2 of 2023, which significantly restricts the legal recognition of interfaith marriages. This situation creates a tension between legal certainty and social reality, and it also affects the legal status of children, who may be categorized as children born out of wedlock, thereby limiting their civil rights protection. From a psychological perspective, children raised in interfaith families face challenges in identity formation, especially in understanding differing religious values received from both parents. Based on Cognitive Dissonance Theory and Erik Erikson’s psychosocial development theory, value differences within the family, along with social pressure from the surrounding environment, may lead to internal conflict, spiritual identity crisis, anxiety, and feelings of alienation. Different parenting styles and social stigma further intensify the psychological burden experienced by children during their developmental process. The research employs a normative-empirical legal method using statutory, conceptual, and sociological approaches. Data were collected through literature review and interviews with relevant informants, and analyzed qualitatively. The findings indicate that although interfaith marriage generates complex legal and psychological consequences, these impacts can be minimized when effective family communication, mutual respect, and supportive social environments are present. This study emphasizes the importance of a legal approach that not only prioritizes legal certainty but also considers humanitarian aspects and the protection of the best interests of the child.